Les régions anglophones du Cameroun, théâtre d’un conflit oublié - Serge Loungou; Serges Meye Ndong (L'Espace Politique)
The North-West and South-West regions of Cameroon, traditionally known as NOSO, are the scene of an armed conflict pitting government forces against pro-independence militias. This asymmetrical confrontation, which has its roots in the vicissitudes of the dual Franco-British colonial heritage, began in October 2017, when activists claiming to be from the Southern Cameroons Ambazonia Consortium United Front (SCACUF) symbolically proclaimed the independence of their regions under the banner of the "Republic of Ambazonia" and created armed militias to fight the presence of the Cameroonian state in the English-speaking zone. The violence linked to this insurgency rapidly turned into a low-intensity armed conflict, the humanitarian and socio-economic consequences of which are considered disastrous after six years of confrontation. The NOSO is the setting for a forgotten conflict, with the understanding that the international community is involved at least in terms of humanitarian care, media attention and political and diplomatic initiatives. This article examines the factors and effects of this neglect. Thus, it appears that the denial and lead screed maintained by Cameroonian actors contribute to hindering the action of the international community in the two regions plagued by armed violence, and that the weak international mobilization associated with the intransigence of the main local protagonists favors the stalemate of the conflict, the specter of which tends to extend beyond the original home of Anglophone Cameroon.